Silymarin and Inflammation: Food for Thoughts - Peter F. Surai; Anton Surai; Katie Earle-Payne (Antioxidants, 2024)
Inflammation is a vital defense mechanism, creating hostile conditions for pathogens, preventing the spread of tissue infection and repairing damaged tissues in humans and animals. However, when inflammation resolution is delayed or compromised as a result of its misregulation, the process proceeds from the acute phase to chronic inflammation, leading to the development of various chronic illnesses. It is proven that redox balance disturbances and oxidative stress are among major factors inducing NF-κB and leading to over-inflammation. Therefore, the anti-inflammatory properties of various natural antioxidants have been widely tested in various in vitro and in vivo systems. Accumulating evidence indicates that silymarin (SM) and its main constituent silibinin/silybin (SB) have great potential as an anti-inflammation agent. The main anti-inflammatory mechanism of SM/SB action is attributed to the inhibition of TLR4/NF-κB-mediated signaling pathways and the downregulated expression of pro-inflammatory mediators, including TNF-α, IL-1β, IL-6, IL-12, IL-23, CCL4, CXCL10, etc. Of note, in the same model systems, SM/SB was able to upregulate anti-inflammatory cytokines (IL-4, IL-10, IL-13, TGF-β, etc.) and lipid mediators involved in the resolution of inflammation. The inflammatory properties of SM/SB were clearly demonstrated in model systems based on immune (macrophages and monocytes) and non-immune (epithelial, skin, bone, connective tissue and cancer) cells. At the same time, the anti-inflammatory action of SM/SB was confirmed in a number of in vivo models, including toxicity models, nonalcoholic fatty liver disease, ischemia/reperfusion models, stress-induced injuries, ageing and exercising models, wound healing and many other relevant model systems. It seems likely that the anti-inflammatory activities of SM/SB are key elements on the health-promoting properties of these phytochemicals.